Social Media Efficacy on Prevention and Control of Covid-19 Pandemic in Ilorin South Local Government Area, Kwara State - Baba Dare Abubakar; Falaye Elijah Kayode; Muhammed Hauwa Abiodun; Adebayo Babatude Samson; Ambali Abdulrasaq (Indonesian Journal of Educational Research and Technology, 2022)
This study investigated social media efficacy on prevention and control of Covid – 19 pandemic in Ilorin South Local Government Area, Kwara State, Nigeria. This study examines the effectiveness of awareness created by Facebook, NCDC messages, and Twitter on prevention and control of Covid – 19 pandemic in Ilorin South LGA, Kwara State. The study adopted a descriptive research design of survey type. A multi-stage sampling technique of stratified and purposive techniques was employed to select 150 respondents for the study. A structured questionnaire was validated and pilot tested with the use of test re-test reliability method and 0.75r were obtained. The findings revealed that awareness created through Facebook, NCDC, and Twitter has many impacts on the prevention and control of the Covid – 19 pandemic. Based on these findings, the study recommends that health officers should encourage people on the need to use social media tools like Facebook, NCDC messages, Twitter, Youtube and soon to gain insight on prevention and control of Covid – 19 pandemic.